PENGARUH PENGUKURAN KINERJA TERHADAP KEPUASAN KERJA DENGAN VARIABEL MODERATING TINGKAT KESULITAN TUJUAN - Erika, Kristina (Jurnal Akuntansi Bisnis, 2014)
Research about the effect of performance measurement on job satisfaction using a variable procedural justice and trust in supervisor has been done previously by Lau and Sholihin (2005). This research is the development of research Lau and Sholihin (2005), that the influence of performance measurement on job satisfaction by considering variable goal difficulty as a moderating variable corresponding with the suggestions of research Lau and Sholihin (2005). Participants in this study were students of Soegijapranata Catholic University Semaran , conditioned as an employee with random sampling. The data analysis technique used ANOVA. From the analysis of data, it was found that employees whose performance is measured using nonfinancial have higher job satisfaction when the goal difficulty set higher than when the goal is a low level of difficulty. While employees whose performance is measured using financial measures have higher job satisfaction when the level of difficulty of the goals set lower than when high levels of goal difficulty. It can be concluded that the influence of performance measurement has joint effect on job satisfaction.